(untitled) (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2022)
This abstract explores the dynamic intersection of tradition and modernity within the realm of Indian art, focusing on the reimagining and reinterpretation of mythology by contemporary artists. India, with its rich cultural heritage and diverse mythological narratives, provides a fertile ground for artists to engage with ancient stories in innovative ways. This study delves into how artists navigate the complex tapestry of mythology, infusing it with contemporary perspectives to create thought-provoking and visually stunning artworks. The research begins by examining the historical context of Indian mythology and its traditional portrayal in art. It then shifts focus to the transformative journey undertaken by contemporary Indian artists who are challenging conventional narratives and embracing new mediums and techniques. The study draws on examples from various art forms, including painting, sculpture, digital art, and installations, to analyze how artists incorporate elements of mythology to comment on contemporary social, political, and cultural issues.